DISKURSUS GENDER: Tela’ah terhadap Pemikiran Amina Wadud - Amaliatul Walidain (Fakultas Adab dan Humaniora UIN Raden Fatah, 2015)
Patriarchal culture has been marginalized women, deny women as khalif fi al-ard, and deny justice teachings promoted by Islam. Amina Wadud focuses on the needs of reform, providing justification from a theological perspective, and look at strategies to build on the reforms in the fight for gender equality. Reconstruction of Islamic understanding of this is within the scope of the research conducted Amina Wadud is related interpretations among Muslims, especially looking at the relationship or the position of women and men. He said problems related about women, referring to the Koran with ideas and ways of thinking are critical in understanding a text (Quran). The focus of attention Wadud is an authority on the interpretation of the principles of feminism, gender justice, verses about social justice and equality of man and some of the factors that led to the marginalization of the role of women.